Interplay of endocrine and psychological factors in IVF/ICSI outcomes: a prospective cohort analysis - Wang, Chao; Li, Qian-Ling; Xu, Yun-Shuai; Cao, Ke-Xin; Zhang, Ya-Qi; Chang, Liang; Tong, Yue; Yang, Ai-Jun; Liu, Zhuang; Zhang, Lin; Lin, Li; Liu, Tour (Frontiers in Endocrinology, 2025)
Infertility poses considerable challenges to both the endocrine system and psychological well-being of affected women. In particular, those undergoing Assisted Reproductive Technology (ART) confront not only physiological demands but also significant psychological stress. Despite the potential interplay between endocrine factors and psychological status in ART outcomes, large-scale investigations remain limited. In this prospective study, we enrolled 493 women undergoing in vitro fertilization and embryo transfer (IVF-ET) or intracytoplasmic sperm injection (ICSI). We collected baseline demographic data, reproductive history, treatment parameters, sleep quality, and psychological status (via validated questionnaires). We then evaluated the relationships between these variables and clinical pregnancy outcomes. Our analysis revealed that perceived stress, as measured by the Perceived Stress Scale (PSS), was a significant predictor of pregnancy outcomes, whereby elevated perceived stress correlated with lower pregnancy rates. In addition, endocrine and clinical parameters—specifically, basal serum LH levels, endometrial thickness on the day of embryo transfer, number of transferred embryos, and the proportion of top-quality embryos—were strongly associated with clinical pregnancy outcomes. These findings underscore the critical interplay between endocrinology and psychology in ART treatment. Elevated perceived stress and specific endocrine factors each exerted a notable impact on IVF/ICSI success, emphasizing the need for integrative approaches that address both physiological and psychological aspects to enhance clinical pregnancy rates.